2011
DOI: 10.1111/j.1537-2995.2011.03294.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of donor fear enhances prediction of presyncopal symptoms among volunteer blood donors

Abstract: Predonation assessment of fear of blood draws may help to identify donors who are most likely to benefit from brief interventions designed to enhance donor coping, reduce risk of presyncopal reactions, and increase donor retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
56
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 26 publications
14
56
0
Order By: Relevance
“…In their study of 210 blood donors, Ando and colleagues 14 suggested that a simple standing test before and after whole blood donation detected heart rate changes that correlated with the risk of vasovagal reactions. France and colleagues 15 showed that assessment of donors' fear or anxiety before the donation may also lead to better prediction of presyncopal symptoms and more effective utilization of specific interventions, such as water ingestion or applied muscle tension for the most susceptible donors. While promising, these pilot studies still need to be tested on a larger scale in blood centers to assess their operational feasibility and effect on the risk of syncope and injuries after whole blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of 210 blood donors, Ando and colleagues 14 suggested that a simple standing test before and after whole blood donation detected heart rate changes that correlated with the risk of vasovagal reactions. France and colleagues 15 showed that assessment of donors' fear or anxiety before the donation may also lead to better prediction of presyncopal symptoms and more effective utilization of specific interventions, such as water ingestion or applied muscle tension for the most susceptible donors. While promising, these pilot studies still need to be tested on a larger scale in blood centers to assess their operational feasibility and effect on the risk of syncope and injuries after whole blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the individual may find the symptoms distressing, thus promoting avoidance of future medical or otherwise important procedures [11,12,29].…”
Section: Introductionmentioning
confidence: 99%
“…Those who expressed fear in the study of experienced donors had a higher percentage of positive BDRIs than those who did not express fear (48 vs. 18%; p < 0.002) [64]. In logistical regression analysis, fear was found to be a strong predictor for a positive reaction using BDRIs.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…44% of the donors (755/1,715) in the high school were afraid, and most had low or moderate amounts of fear. The proportion with fear was higher in first-time donors (495/855 (58%)) than in repeat donors (260/860 (30%)), but both groups had higher fear rate proportions than the general donor population (15%) [64,65]. …”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
See 1 more Smart Citation